IMPLEMENTASI PROGRAM ADMINISTRASI KEPENDUDUKAN DI KELURAHAN BABATAN KECAMATAN WIYUNG KOTA SURABAYA: (STUDI PADA PELAYANAN AKTA KELAHIRAN) - Indriani, Shelvia Dwi; Rahaju, Tjitjik (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
The population administration program is a Surabaya City government policy to optimize services and ensure that rights ownership of citizen identity can be accessed easily and quickly. Babatan subdistrict is one of the subdistricts implementing the program and problems were found the low level of birth certificate ownership and there were still people who did not know about the program. This research analyzes the implementation of the program in Babatan Subdistrict birth certificate service, using a descriptive method with a qualitative approach. Data was collected through observation, interviews, and documentation, with both primary and secondary data sources. Data analysis techniques through data collection, data reduction, data presentation and verification. The focus of this research by Edward III theory: communication, resources, disposition, bureaucratic structure. The results of research on communication indicators still found obstacles as information distribution to the public is uneven. In the resource indicators, there were issues with facilities, such as computers lacking camera features, and problems with the Klampid Application. The disposition indicator showed a strong commitment to program implementation, while the bureaucratic structure followed Standard Operating Procedures (SOP). Recommendations include intensive communication and raising awareness about adult birth certificate ownership, adding webcams to computers, and officers being more active in communicating if there are application problems that result in delays in completion.